Analytics on Service Quality in Spectator Sports - Ahmet Ozkul; Gazi Duman (Journal of Applied Sports Management, 2022)
Spectator sport events are made possible by the contributions of many different participants ranging from fans and players to coaches, managers and sponsors. Through the lens of co-creation of value in the spectator sports, we discuss how sport analytics can relate to spectator sport service quality by collecting and analyzing data from each participating actor.
Keywords: Analytics; Sport Service Quality; Coproduction; Co-creation